2016
DOI: 10.1371/journal.pone.0153170
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplant Recipients Treated with Calcineurin-Inhibitors Lack Circulating Immature Transitional CD19+CD24hiCD38hi Regulatory B-Lymphocytes

Abstract: BackgroundCD19+CD24hiCD38hi transitional immature B-lymphocytes have been demonstrated to play an important role in regulating the alloimmune response in transplant recipients. Here, we analyzed the effect of calcineurin inhibition on these peripherally circulating regulatory B-cells (Breg) in renal transplant recipients receiving cyclosporine A (CsA) or tacrolimus.MethodsPBMCs from healthy subjects (HS) (n = 16) and renal transplant recipients (n = 46) were isolated. Flow cytometry was performed for CD19, CD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 30 publications
(41 reference statements)
3
35
1
1
Order By: Relevance
“…In humans, the memory B10 subpopulation displaying the CD19 + CD24 hi CD27 + phenotype has been shown to suppress monocyte proinflammatory cytokines by producing IL‐10 in in vitro functional assays . The transitional B10 subpopulation with the CD19 + CD24 hi CD38 hi phenotype suppresses the differentiation of Th1 cells by producing IL‐10 after stimulation at the cell surface and signal activation . Unfortunately, at the moment, purification of B10 cells is technically challenging, which limits the in‐depth exploration of their functions.…”
Section: Regulatory Functions Of B Cells In Transplantationmentioning
confidence: 99%
“…In humans, the memory B10 subpopulation displaying the CD19 + CD24 hi CD27 + phenotype has been shown to suppress monocyte proinflammatory cytokines by producing IL‐10 in in vitro functional assays . The transitional B10 subpopulation with the CD19 + CD24 hi CD38 hi phenotype suppresses the differentiation of Th1 cells by producing IL‐10 after stimulation at the cell surface and signal activation . Unfortunately, at the moment, purification of B10 cells is technically challenging, which limits the in‐depth exploration of their functions.…”
Section: Regulatory Functions Of B Cells In Transplantationmentioning
confidence: 99%
“…The “stable” population appears to be the most clinically relevant as future potential candidates for minimization protocols. Nevertheless, because immunosuppression has been shown to alter gene expression 41, 42, 52, 53 and particularly circulating B cells 54 , immunosuppression may affect cSoT. Unfortunately, samples before immunosuppression withdrawal are not available notably as TOL are mainly non-compliant and as intentional immunosuppression withdrawal trials have failed 18, 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Tebbe et al . reported that calcineurin‐inhibitors in renal transplant recipients reduced the numbers of B cells, especially the immature transitional CD19 + CD24 hi CD38 hi regulatory B cells and IL‐10‐producing B cells. Rebollo‐Mesa et al .…”
Section: B Cell Signature and Tolerance In Humansmentioning
confidence: 99%